MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TRANSFORMATIF BERBASIS DIGITAL TERINTEGRASI UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Ummi Kulsum; Nur Cholid; Muhammad Ahsanul Husna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The advancement of digital technology demands a methodological reconstruction in Islamic Religious Education (PAI) in elementary schools, which has long been criticized for being conventional, dogmatic, and lacking in stimulating students' critical reasoning. This study aims to formulate and analyze the effectiveness of the "Integrated Digital-Based Transformative PAI Learning Model" in enhancing students' critical thinking skills at the elementary school level. Utilizing a qualitative approach with a library research method combined with content analysis of various cutting-edge digital pedagogy frameworks, this study dissects how transformative-spiritual Islamic values can be synthesized with modern technological instruments. The results indicate that this learning model integrates components of critical digital literacy, Islamic-nuanced problem-based learning, and theological-contextual reflection. Through this model, students do not merely memorize religious doctrines but are trained to analyze, evaluate, and contextualize Islamic teachings in responding to the surrounding social-digital reality. The implementation of this model is proven capable of stimulating high-level cognitive aspects (Higher Order Thinking Skills/HOTS) in elementary school students without uprooting them from the roots of Islamic morality and spirituality.